Pharmacological Evaluation of 3-Carbomethoxy Fentanyl in Mice - Zeljko Mikovic; Marko Kadija; Cedomir Vucetic; Katarina Savic Vujovic; Ljiljana Dosen-Micovic; Milovan Ivanovic; Sonja Vuckovic; Milica Prostran (MDPI AG, 2011)
In many animal species, as well as in humans, high doses of fentanyl (F) produce marked neurotoxic effects, such as muscular rigidity and respiratory depression. The antinociception (hot-plate test), impairment of motor coordination (rotarod test) and acute toxicity of intraperitoneal newly synthesized analogs, (±)cis-3-carbomethoxy- fentanyl (C) and (±)trans-3-carbomethoxyfentanyl (T) were evaluated in mice. The compounds tested induced antinociception, impairment of performance on the rotarod, and lethality in a dose-dependent manner. The relative order of antinociceptive potency was similar to motor impairment potency, as well as lethality: F > C > T. Naloxone hydrochloride (1 mg/kg; sc) abolished all the effects observed, suggesting that they are mediated via opioid receptors, most probably of m type. There were no significant differences between the therapeutic indices of F, C and T. It is concluded, the introduction of 3-carbomethoxy group in the piperidine ring of the fentanyl skeleton reduced the potency, but did not affect tolerability and safety of the compound.